The genetic causal association between arthritis and low back pain - Aimin Gong; Daniel Yang; Mengjie Zeng (JOR Spine)
Abstract Background Arthritis and low back pain (LBP) are prevalent musculoskeletal conditions with a perceived association. Previous observational studies have suggested a possible link between arthritis and LBP, but causality has not been firmly established. Methods The analysis involved data from a meta‐analysis of genome‐wide association studies sourced from the UK Biobank Genetics resources on rheumatoid arthritis (RA), osteoarthritis (OA) at any site, knee osteoarthritis (KOA), hip osteoarthritis (HOA), and LBP. Two‐sample Mendelian randomization analysis was utilized to evaluate the causal link between arthritis and LBP. The primary method employed was inverse‐variance weighting (IVW), with additional techniques such as MR‐Egger, weighted median, Cochran Q statistic, and leave‐one‐out analysis used to identify heterogeneity and pleiotropy. Results Genetically determined RA exhibited a causal impact on LBP (Weighted median: odds ratio [OR] = 1.094, 95% confidence interval [CI] 1.002–1.195, p = 0.043). Furthermore, OA at any site and KOA showed causal associations with LBP (Inverse variance weighted: OR = 1.089, 95% CI 1.011–1.173, p = 0.026) and (OR = 1.0004, 95% CI 1.000–1.008, p = 0.019), respectively. Additionally, HOA was also linked causally with an elevated risk of developing LBP (Weighted median: OR = 1.002, 95% CI 1.000–1.004, p = 0.049; Inverse variance weighted: OR = 1.002, 95% CI 1.001–1.004, p = 0.003). Conclusions This study offers genetic evidence supporting the causal relationship between RA, OA at any site, KOA, HOA and the increased risk of LBP, especially highlighting the significant impact of HOA.